Deep Investigation of Arabidopsis thaliana Junk DNA Reveals a Continuum between Repetitive Elements and Genomic Dark Matter - Maumus, Florian (Public Library of Science, 2014)
Eukaryotic genomes contain highly variable amounts of DNA with no apparent function. This so-called junk DNA is composed of two components: repeated and repeat-derived sequences (together referred to as the repeatome), and non-annotated sequences also known as genomic dark matter. Because of their high duplication rates as compared to other genomic features, transposable elements are predominant contributors to the repeatome and the products of their decay is thought to be a major source of genomic dark matter. Determining the origin and composition of junk DNA is thus important to help understanding genome evolution as well as host biology. In this study, we have used a combination of tools enabling to show that the repeatome from the small and reducing A. thaliana genome is significantly larger than previously thought. Furthermore, we present the concepts and results from a series of innovative approaches suggesting that a significant amount of the A. thaliana dark matter is of repetitive origin. As a tentative standard for the community, we propose a deep compendium annotation of the A. thaliana repeatome that may help addressing farther genome evolution as well as transcriptional and epigenetic regulation in this model plant.